Karakteristik Morfologis Sufiks -na Bahasa Madura Dialek Sumenep - Ahmad Faizal; Ahmad Al Farisi; Taufiqur Rahman; Mas’odi (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
Madurese is one of the languages used by the Madurese people themselves. Madurese has four dialects, including the Bangkalan dialect, the Sampang dialect, the Pamekasan dialect and the Sumenep dialect. The dialects of each region have their own characteristics. However, in language it is not very different. Apart from the four dialects above, there are several areas outside Madura Island that also use Madurese, such as Jember, Banyuwangi and Probolinggo. In this research the author will discuss or describe the Morphological Characteristics of the Madurese Suffix -na in the Sumenep dialect which includes function, form and meaning. In this research, the author used qualitative descriptive research. Data collection was carried out using analysis or introspection methods. The author is a native speaker of the Sumenep dialect of Madurese. Therefore, the author uses analysis or introspection methods in collecting data. In order not to expand, the researcher focuses more on the scope of this research on the Morphological Characteristics of the Madurese Suffix -na. The aim of this research is to describe the use of the suffix -na in the Madurese dialect of Sumenep.